THE IMPACT OF ENVIRONMENTAL CONFLICT AND EDUCATION ON SOCIAL ECONOMIC DEVELOPMENT IN SOUTH SUDAN - Riak , Dr Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study aimed at providing a broader understanding of how ethnic conflict and education affect social-economic development of South Sudan. The objectives of the study were to examine the relationship between ethnic conflict and Social-economic development of South Sudan, analyse the relationship between Education and Social-economic development of South Sudan and to study the factor structure of ethnic conflict and Education on Social-economic development of South Sudan.The study employed a case study and descriptive design while using qualitative and quantitative approaches. The study population was 340, selected using purposive and simple random sampling technique. The sample size determination was made using Krejcie and Morgan Table (1970) formula. The sample size was 211. The data analysis was made using Statistical package for social scientists (SPSS 18). The major findings of the study were that there was a positive relationship between; ethnic conflict and social-economic development (r = 0.827, P-value < 0.01), Education and Social-economic development (r = 0.916, P-value < 0.01) and lastly variables explained R= 0.644) a combination of armed conflict and education in assessing the level to which they can predict the level of social-economic development, such that unit change in a possibility of an ethnic conflict twill contribute to a change in the possibility of social-economic development by (.668) while a one unit change in education systems will contribute to a change in the social-economic development of the County like Juba and the whole Country at large (.408).The study recommends that there should be peace building measures that directly focus on how to combat ethnic conflict especially the fighters, a proper recommendable approach would be fostering Amnesty programs for fighters to ensure peace building, all counties, organizations and stakeholders should invest heavily in educating their staff and sensitizing their beneficiaries about the need for peace building and where need be, set up education programs for their staff in a bid to build their competence and that peace building to end conflicts should be advocated for through all channels right from curbing ethnic conflict, engaging more organizations and most importantly with strong education systems.